The systemic management of central nervous system metastases and leptomeningeal disease from advanced lung, melanoma, and breast cancer with molecular drivers: An Australian perspective. Issue 6 (3rd March 2022) - Senko, Clare; Gunjur, Ashray; Balasubramanian, Adithya; Gan, Hui K.; Parakh, Sagun; Cher, Lawrence
Abstract: The advent of systemic therapies with high intracranial efficacy in recent years is changing the therapeutic paradigm and renewing interest in the management of central nervous system (CNS) and leptomeningeal metastases from solid organ tumors. CNS metastases have traditionally heralded a dismal prognosis with median survival of 3–10 months, and were primarily treated with local therapeutic modalities, such as surgery or radiation therapy. Although these modalities still have a role in the management of CNS disease, newer agents, such as small molecule tyrosine kinase inhibitors and immune‐checkpoint inhibitors, are now paving the way as an alternative therapeutic option for those with oligometastatic or low‐volume intracranial disease, potentially eliminating or delaying the need for local treatment modalities in this setting. Herein, we summarize the systemic treatments with proven intracranial efficacy, currently approved for use in Australia for advanced mutation‐driven non‐small cell lung cancer, melanoma, and breast cancer, as well as novel agents in preclinical and clinical trial development.